2013
DOI: 10.1002/prot.24281
|View full text |Cite
|
Sign up to set email alerts
|

Inositol phosphates compete with nucleic acids for binding to bovine leukemia virus matrix protein: Implications for deltaretroviral assembly

Abstract: The matrix (MA) domain of retroviral Gag proteins plays a crucial role in virion assembly. In human immunodeficiency virus type 1 (HIV-1), a lentivirus, the presence of phosphatidylinositol-(4,5)-bisphosphate triggers a conformational change allowing the MA domain to bind the plasma membrane (PM). In this study, the MA protein from bovine leukemia virus (BLV) was used to investigate the mechanism of viral Gag binding to the membrane during replication of a deltaretrovirus. Fluorescence spectroscopy was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…Our competition assays with IP6 demonstrate that HTLV-2 MA is competed off NAs even more effectively than HIV-1 MA and suggest that the MA-IP6-interacting surface likely overlaps the MA-NA binding site. Similar results were recently reported for BLV MA (52). IP6 possesses more negative-charge density than the head group of PI(4,5)P 2 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our competition assays with IP6 demonstrate that HTLV-2 MA is competed off NAs even more effectively than HIV-1 MA and suggest that the MA-IP6-interacting surface likely overlaps the MA-NA binding site. Similar results were recently reported for BLV MA (52). IP6 possesses more negative-charge density than the head group of PI(4,5)P 2 .…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to nonspecific binding interactions of MA with longer nucleic acid sequences. A recent study of BLV MA showed high-affinity (10 to 20 nM) binding to RNAs derived from the BLV genome, supporting a conservation of function among deltaretroviral MA proteins (52). In contrast, previous work has shown that HIV-1 MA is not required for specific gRNA binding (46).…”
Section: Discussionmentioning
confidence: 84%
“…The failure of IP6 to stimulate RSV Gag chaperone function likely is due to the weak binding of the MA domain to NA rather than to lack of MA-IP interaction based on our finding that IP6 competes with RNA for binding to MA. Thus, similar to other retroviral MA domains (20,56,57), RSV MA is capable of binding IPs, but unlike the case in HIV-1, this binding does not stimulate chaperone function because MA is so weakly bound to NA in the first place. Furthermore, finding that the RSV Gag-NA interaction was not disrupted by IP6 in vitro suggests that Gag is so tightly bound to NA via the NC domain that IP6 is not an effective competitor.…”
Section: Discussionmentioning
confidence: 91%
“…The lower overall net positive charge of RSV MA is also consistent with our observation that RSV MA has a very weak binding affinity for RNA relative to HIV-1 H6.MA (Table 3). Interestingly, the pI of the human T-cell leukemia virus type 2 (HTLV-2) MA protein (9.51) is even higher than that of HIV-1 MA, and we recently showed that, similar to bovine leukemia virus MA (56), this deltaretroviral MA protein binds RNA oligonucleotides derived from HTLV-2 gRNA with even higher affinity (ϳ70 nM at 50 mM NaCl) than HTLV-2 NC (57). Thus, retroviruses appear to possess a wide spectrum of MA-NA binding capabilities, which may have evolved due to distinct mechanisms of action during virus assembly and/or postentry.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding BLV NC was PCR-amplified from a BLV proviral plasmid (a gift from Dr. Kathleen Boris-Lawrie, Department of Veterinary Biosciences, The Ohio State University) and ligated into pET32a (EMD Millipore, Billerica, MA) using standard molecular biology protocols. BLV NC was expressed as a thioredoxin fusion protein; culture growth and protein expression were performed essentially as described previously [29]. Trx-BLV NC was purified from frozen cell pellets using Ni 2þ -affinity chromatography.…”
Section: Na and Protein Preparationmentioning
confidence: 99%